2019
DOI: 10.1016/j.jped.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and activity, metabolic profile, adipokines and endothelial function in children

Abstract: This study showed that endothelial dysfunction is already present in obese children, suggesting a predisposition to atherosclerotic disease. Moreover, HDL cholesterol levels were correlated with physical fitness, regardless of body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…The increase in childhood obesity worldwide is recognized as one of the most severe public health problems. The evidence of the association between childhood obesity and parameters of MetS is increasing (7,16,17). Adipocytokines and genetic background are known to be important in the pathogenesis of MetS (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in childhood obesity worldwide is recognized as one of the most severe public health problems. The evidence of the association between childhood obesity and parameters of MetS is increasing (7,16,17). Adipocytokines and genetic background are known to be important in the pathogenesis of MetS (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…HPF assessment, therefore, may have important implications in the prevention of chronic diseases. Previous studies have shown that HPF can predict multiple risk factors for CVD [12][13][14]. Body composition is better at distinguishing between fat mass and fat-free mass than BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and high blood pressure contribute to the deterioration of vascular reactivity [ 56 ] and carotid obstruction in children [ 57 ]. The effects of swimming on vascular function in children and adolescents have been neglected by current research.…”
Section: Discussionmentioning
confidence: 99%